The Business Cycle and Entry into Early American Banking - Bodenhorn, Howard (The Review of Economics and Statistics, 1993)
The conditions of entry have been the focus of a large and growing number of theoretical and empirical studies. Several recent papers have developed new techniques for the study of entry into manufacturing industries. This paper finds those same techniques useful for the study of entry into early American financial markets. Market characteristics commonly found to influence the rate of industrial entry, as well as the course of the business cycle, are found to be important in the timing of entry into nineteenth-century financial markets. Copyright 1993 by MIT Press.